Comparative Study Between Blood Glucose Meters in a Maternity Center - Rihab Ayadi; Monia Tlig; Imène Ben Jdida; Kaouther Zribi; Linda Khefacha; Mouna Sassi; Balsam Kacem; Amani Chérif (Women's Health Reports)
Background: Monitoring of diabetes by measuring capillary blood glucose using a glucometer. Objectives: To compare the three most used glucose meters in diabetic patients in a maternity and neonatal center in terms of repeatability, accuracy, and stability. Methodology: A comparative study on 100 diabetic patients admitted to the various departments of a maternity and neonatal center. For each patient, a capillary measurement was made using each of the three glucometers to be tested (Accucheck®, On Call® and Bionime®) as well as a blood glucose on venous blood, performed in the laboratory using the Siemens X brand plus® PLC (reference method). The same sample was used to carry out all measurements. Results and Conclusions: The Accucheck® brand reader and the On Call® brand thus, show a better correlation for open and closed bottles of test strips’storage, compared with the Bionime® brand reader. We found that the Accucheck® and On Call® readers are comparable in terms of reliability of results and are better than the Bionime® brand reader. We have found that, first using closed vials give more accurate results for glycemia readers and also, On Call® and Accucheck® brand readers are more reliable and accurate than the Bionime® brand reader.